Simple Evaluation On Wound Healing Properties Of Lygodium Japonicum Leaf Extract - Muhamad Fakhri, Azmi (Universiti Sains Malaysia, 2006)
Simple evaluation on the wound healing activities on Sprague-Dawley rats using the preparation of crude leaf extract of Lygodium japonicum was done. The crude extract (50 mg) was applied to the surface of wounds ones, three (3) consecutive times, whereas for control rats were not treated at all. The contraction and tensile strength were measured to evaluate the effects of Lygodium japonicum on wound healing. The results showed no significant difference in wound constraction and tensile strength using the Lygodium japonicum crude leaf extract compared to control experiment.